Catalytic Reforming of Iraqi Naphtha over Pt-Ti / HY Zeolite Catalyst - Ahmedzeki, Nada S.; Al-Tabbakh, Ban A. (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
In the present work, zeolite Y has been synthesized successfully by sol-gel method.Zeolite was synthesized by crystallization of the final gel which consist from seeding and feed stock gels at  85 oC. HY zeolite was prepared by an ion exchange process with ammonium chloride solution and then loaded with different percentages of  platinum and titanium by the wet - impregnation method.X-ray Diffraction (XRD), X-ray Florescence (XRF), Scanning Electron Microscopy (SEM), BET surface area and, Crushing strength were used to characterize the synthesized and prepared catalysts . Results showed high crystallinity  90%  with silica to alumina ratio 5 for HY, high surface area of 600 m2/g and pore volume of 0.38 cm3/g.The activity of the prepared zeolite was investigated using a pilot plant unit for the catalytic reforming of Iraqi heavy naphtha. All prepared catalysts were investigated at temperatures of 490,500 and 510oC ,pressure of 20 bar, H2 /HC  ratio 3 and LHSV 1.4.hr-1.Reformate was produced with 86 RON and 94% yield at 510ºC and 20 bar using 0.13 wt.% Pt - 0.75 wt.% Ti  loaded on synthesized HY.